Pengembangan Aplikasi Diagnostik Kerusakan Kendaraan Roda Empat Berbasis Android Menggunakan MIT App Inventor Sebagai Media Pembelajaran pada Mata Kuliah Diagnosis dan Perbaikan Kendaraan di Universitas Negeri Makassar - Muhammad Mahdinul Bahar; Iriani Faisal; Marselona Longgo (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
The rapid advancement of automotive technology requires vocational education institutions to be adaptable in updating their teaching materials and methods. In the Department of Automotive Engineering Education, Faculty of Engineering, Makassar State University, students’ ability to detect and diagnose four-wheeled vehicle malfunctions is often hindered by limited physical practice facilities and difficulties in identifying engine malfunction characteristics through auditory means. This development research aims to produce an Android-based four-wheeled vehicle damage diagnostic application using the MIT App Inventor visual platform, which functions as an interactive self-learning medium. The development approach uses the Waterfall model, which includes requirements analysis, system design, implementation, testing, and maintenance. The developed application integrates a database of abnormal vehicle acoustic spectra as a practical guide for identifying damage. Validation results by subject matter experts yielded a feasibility percentage of 93.00%, by media experts of 90.00%, and a limited pilot test with students yielded a positive response rate of 88.73%, placing this application in the “highly feasible” category for use in vocational learning processes.